Check GMAT Club Decision Tracker for the Latest School Decision Releases https://gmatclub.com/AppTrack

 It is currently 25 May 2017, 01:56

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# If m^(-1) = -1/3 then m^(-2) is equal to

Author Message
TAGS:

### Hide Tags

Manager
Joined: 02 Dec 2012
Posts: 178
Followers: 6

Kudos [?]: 2695 [0], given: 0

If m^(-1) = -1/3 then m^(-2) is equal to [#permalink]

### Show Tags

20 Dec 2012, 07:23
6
This post was
BOOKMARKED
00:00

Difficulty:

5% (low)

Question Stats:

82% (01:28) correct 18% (00:39) wrong based on 1042 sessions

### HideShow timer Statistics

If m^(-1) = -1/3 then m^(-2) is equal to

(A) -9
(B) -3
(C) -1/9
(D) 1/9
(E) 9
[Reveal] Spoiler: OA
Math Expert
Joined: 02 Sep 2009
Posts: 38860
Followers: 7728

Kudos [?]: 106076 [1] , given: 11607

Re: If m^(-1) = -1/3 then m^(-2) is equal to [#permalink]

### Show Tags

20 Dec 2012, 07:25
1
KUDOS
Expert's post
3
This post was
BOOKMARKED
If m^(-1) = -1/3 then m^(-2) is equal to

(A) -9
(B) -3
(C) -1/9
(D) 1/9
(E) 9

$$m^{-1} = -\frac{1}{3}$$ --> $$\frac{1}{m}=-\frac{1}{3}$$ --> $$m=-3$$ --> $$m^{-2}=\frac{1}{m^2}=\frac{1}{9}$$.

_________________
SVP
Status: The Best Or Nothing
Joined: 27 Dec 2012
Posts: 1857
Location: India
Concentration: General Management, Technology
WE: Information Technology (Computer Software)
Followers: 51

Kudos [?]: 2168 [1] , given: 193

If m^(-1) = -1/3 then m^(-2) is equal to [#permalink]

### Show Tags

27 Feb 2014, 20:20
1
KUDOS
If m^(-1) = -1/3 then m^(-2) is equal to

(A) -9
(B) -3
(C) -1/9
(D) 1/9
(E) 9

$$\frac{1}{m} = \frac{-1}{3}$$

Squaring both sides

$$\frac{1}{m^2} = \frac{1}{9} =$$Answer = D
_________________

Kindly press "+1 Kudos" to appreciate

GMAT Club Legend
Joined: 09 Sep 2013
Posts: 15434
Followers: 649

Kudos [?]: 208 [0], given: 0

Re: If m^(-1) = -1/3 then m^(-2) is equal to [#permalink]

### Show Tags

11 Sep 2015, 12:33
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________
Target Test Prep Representative
Affiliations: Target Test Prep
Joined: 04 Mar 2011
Posts: 895
Followers: 34

Kudos [?]: 507 [0], given: 2

Re: If m^(-1) = -1/3 then m^(-2) is equal to [#permalink]

### Show Tags

28 Jun 2016, 05:48
If m^(-1) = -1/3 then m^(-2) is equal to

(A) -9
(B) -3
(C) -1/9
(D) 1/9
(E) 9

Since we know that m^-1 = -1/3 and m^-2 = (m^-1)^2, then m^-2 = (-1/3)^2 = 1/9.

_________________

Jeffery Miller

GMAT Quant Self-Study Course
500+ lessons 3000+ practice problems 800+ HD solutions

VP
Joined: 12 Sep 2015
Posts: 1430
Followers: 138

Kudos [?]: 1614 [1] , given: 327

Re: If m^(-1) = -1/3 then m^(-2) is equal to [#permalink]

### Show Tags

27 Jul 2016, 07:53
1
KUDOS
Top Contributor
If mˉ¹ = -1/3 then mˉ² is equal to

(A) -9
(B) -3
(C) -1/9
(D) 1/9
(E) 9

Some good solutions here.
Here's one more approach:

CONCEPT: b^(-n) = 1/(b^n)

Given: mˉ¹ = -1/3
Rewrite as: 1/m = 1/(-3)
We can see that m = -3

So, mˉ² = 1/(m²) = 1/(-3)² = 1/9

[Reveal] Spoiler:
D

RELATED VIDEO

_________________

Brent Hanneson – Founder of gmatprepnow.com

BSchool Forum Moderator
Joined: 12 Aug 2015
Posts: 2135
Followers: 73

Kudos [?]: 608 [0], given: 553

Re: If m^(-1) = -1/3 then m^(-2) is equal to [#permalink]

### Show Tags

29 Jul 2016, 11:52
M^-1=-1/3=> M=-3
hence M^-2=1/9
Smash D
_________________

Give me a hell yeah ...!!!!!

Intern
Joined: 12 Jun 2016
Posts: 27
Location: India
Concentration: Entrepreneurship, Finance
GPA: 3.76
WE: Information Technology (Computer Software)
Followers: 0

Kudos [?]: 10 [1] , given: 18

Re: If m^(-1) = -1/3 then m^(-2) is equal to [#permalink]

### Show Tags

29 Jul 2016, 12:14
1
KUDOS
m^(-1) = -(1/3)
Squaring both sides
m^(-2) = 1/9

Ans. D
Intern
Joined: 26 Sep 2016
Posts: 7
Followers: 0

Kudos [?]: 0 [0], given: 2

Re: If m^(-1) = -1/3 then m^(-2) is equal to [#permalink]

### Show Tags

27 Sep 2016, 14:26
$$m^-1 = \frac{-1}{3}$$

$$\frac{1}{m} = \frac{-1}{3}$$

By cross multiplication

$$-m = 3$$

Squaring both sides

$$m^2 = 9$$

So $$m^-2 = \frac{1}{9}$$
Re: If m^(-1) = -1/3 then m^(-2) is equal to   [#permalink] 27 Sep 2016, 14:26
Similar topics Replies Last post
Similar
Topics:
1 Which of the following is equal to 3^m7^m-1? 5 09 Mar 2017, 03:49
If m ≠ 0 and m - 1+2m^2/2m =y/x, then y is...= 5 15 May 2014, 06:39
35 If m and n are integers and 36/3^4 = 1/3^m + 1/3^n , what is 15 05 Nov 2016, 18:03
5 The ratio 2 to 1/3 is equal to the ratio 9 12 Jun 2016, 04:34
2 If m^(-1) = -1/3 then m^(-2) is equal to 6 16 May 2016, 02:31
Display posts from previous: Sort by